Five species of Liparis (Orchidaceae) newly recorded for Thailand - Tetsana, Naiyana; Pedersen, Henrik Æ.; Sridith, Kitichate (Thai Forest Bulletin (Botany), 2014)
During work on a forthcoming new revision of Liparis in Thailand, fi ve new national records were discovered, and details on the Thai occurrences are reported in this paper. Three of the newly recorded species are terrestrials that only produce leaves in the rainy season. Thus, (1) L. acutissima Rchb.f. (also known from Cambodia, Laos and Vietnam) is reported from Phu Wua Wildlife Sanctuary, province of Bueng Kan; (2) L. sootenzanensis Fukuy. (also known from Taiwan and Vietnam), is reported from Phu Hin Rong Kla National Park, province of Phitsanulok; and (3) L. stenoglossa C.S.P.Parish & Rchb.f. (previously considered endemic to Myanmar) is reported from Wat Tham Pha Sawan, Nong Hin, province of Loei. The two remaining species are epiphytes that bear leaves all the year round. Thus, (4) L. elegans Lindl. (widespread in Malesia) is reported from Khao Sok National Park in province of Surat Thani and from Khao Chet Yot in province of Trang; and (5) L. vestita Rchb.f. (previously known from India only) is reported from Amphoe Rong Kwang in province of Phrae and from two parts of Khao Yai National Park (situated in the provinces of Nakhon Nayok and Prachin Buri, respectively). The newly recorded species are illustrated by colour photos, and morphological descriptions based on Thai material are provided together with lists of synonyms and supplementary references to the literature. The name L. elegans Lindl. is lectotypifi ed.